Post-approaches to education and the arts: Putting theories to work in arts educational practices - Sofia Jusslin; Linnea Bodén; Lena O Magnusson; Tone Pernille Østern (Cappelen Damm Akademisk NOASP, 2022)
This special issue explores how post-approaches to education and the arts emphasize learning, teaching, and knowledge-production in the arts as performative processes of becoming in-between humans and other materialities in a more-than-human world. Moreover, the articles included in the special issue reveal that such an endeavor calls for new ways of doing research through post-qualitative and practice-led research methodologies.